Binswanger: A Dialogue between Phenomenology and Psychoanalysis (Phenomenology, Humanities and Sciences, 2022)
This article proposes to carry out an analysis of the development of the thought of the Swiss psychiatrist Ludwig Binswanger, from which the relationship between phenomenology and psychoanalysis will be discussed. Through the knowledge of his theoretical motivations and his friendship with Sigmund Freud, we seek to point out how psychoanalysis influenced his theory, expressed in some of his concepts and other points that received mutual influence. It is concluded that both in the theoretical-professional and in the personal sphere, Binswanger represents an articulation between the two theories, which locates his theory as a result of an effective dialogue between phenomenology and psychoanalysis.
Keywords: Psychoanalysis; Phenomenology; Binswanger